2020
DOI: 10.1007/s40620-020-00774-5
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes on safety and efficacy of left atrial appendage occlusion in end stage renal disease patients undergoing dialysis

Abstract: Background In patients with end stage renal disease and atrial fibrillation (AF), undergoing chronic dialysis, direct oral agents are contraindicated and warfarin does not fully prevent embolic events while increasing the bleeding risk. The high hemorrhagic risk represents the main problem in this population. Aim of the study was to estimate the safety and efficacy for thromboembolic prevention of left atrial appendage (LAA) occlusion in a cohort of dialysis patients with AF and high hemorrhagic risk. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 34 publications
1
36
0
8
Order By: Relevance
“…Additionally, recent studies have explored its efficacy for thromboembolic prevention in patients with end-stage renal disease [ 131 , 132 , 133 , 134 , 135 ]. Although not yet confirmed in large studies, these preliminary findings are highly promising.…”
Section: Non-anticoagulative Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent studies have explored its efficacy for thromboembolic prevention in patients with end-stage renal disease [ 131 , 132 , 133 , 134 , 135 ]. Although not yet confirmed in large studies, these preliminary findings are highly promising.…”
Section: Non-anticoagulative Approachesmentioning
confidence: 99%
“…Several antithrombotic strategies have been empirically adopted in clinical practice to avoid this worrisome complication [ 126 , 127 , 136 , 137 ]. To date, the most common approach is based on the use of aspirin, initially with clopidogrel and then alone, to prevent activation of platelets coming in contact with the atrial surface of the device until complete endothelialization is achieved [ 131 , 132 , 133 , 134 , 135 ]. Randomized clinical trials are needed to identify the best antithrombotic therapy to prevent device-related thrombosis and explore the efficacy of LAAO in high-risk populations with a reduced safety margin between stroke prevention and bleeding risk (e.g., end-stage CKD, elderly).…”
Section: Non-anticoagulative Approachesmentioning
confidence: 99%
“…However, as the experience of various centers increased, complications declined (e.g., the results of PROTECT-AF at four years [8]: the rate of composite primary safety events was similar in the two groups -3.6 events per 100 patient-years in the device group vs. 3.1 in the warfarin group (HR, 1.21; 95% CI, 0.78-1.94, P = 0.41). It is also important to note that, even in such a fragile population as that of Genovesi et al (two major peri-procedural complications were recorded in 92 patients), the complication rate is certainly acceptable, even if not negligible [20].…”
Section: Comparing the Current Evidencementioning
confidence: 90%
“…Indeed, in this population, where the prevalence of AF is very high, VKAs are associated with a high incidence of bleeding, and DOACs are contraindicated [7]. Initial encouraging data suggest that LAAO occlusion in dialysis patients has a good efficacy and safety profile [20]. A Spanish study is currently underway in ESRD patients (WATCH-HD, NCT03446794), including two arms, the Watchman device vs. no-therapy.…”
Section: Laao -A Veritable Solution For Selected Patientsmentioning
confidence: 99%
“… 14 , 15 Additionally, few retrospective and largely single-center studies have demonstrated conflicting outcomes after LAAO with Watchman implantation in AF patients with CKD and ESRD. 17 , 18 , 19 , 20 The purpose of the current study is to assess the association of CKD or ESRD with risk of procedural complications and inpatient adverse events in AF patients implanted with a Watchman device from a large, nationally representative, and contemporary sample of the United States population.…”
Section: Introductionmentioning
confidence: 99%